ANALISIS DAN PERANCANGAN SISTEM INFORMASI MANAJEMEN ASET PADA KANTOR BADAN METEOROLOGI, KLIMATOLOGI DAN GEOFISIKA (BMKG) PROVINSI JAMBI - sari, Patma Ratna; Devitra, Joni (LPPM Universitas Dinamika Bangsa, 2017)
The Office of Meteorology, Climatology and Geophysics of Jambi Province is a public service whosemain task is to provide flight meteorology information for aviation safety as well as providing daily andweekly weather forecast information. Asset management at BMKG Office of Jambi Province is donemanually so that asset management system performance is still not optimal. One way of assetmanagement can be more optimal is to use information systems. Asset management research is carriedout at the planning, procurement, receiving, deployment, depreciation, deletion and administration stage.This study produces a prototype system that describes the functionality of planning, procurement,acceptance, use, depreciation, deletion and administration of assets at the Office BMKG Jambi Province.The method used is object-oriented approach using UML (Unified modeling language) that is use casediagram, class diagram and Activity diagram. This research produce a prototype that can be implementedfurther to produce asset management information system that can be implemented at Office BMKG JambiProvince.